An Investigation of Education Sector Analyzing Leadership Style and Employees’ Performance - Jalil, Abdul; Abbasi, Zareen; Chachar, Ayaz Ahmed (Annals of Human and Social Sciences, 2024)
Schools are vital establishments where the next generation receives knowledge and skills. The leadership is to determine the effectiveness of education systems at all levels, dealing with mutual consensus. The objective of this research study was to analyze the impact of Head Teachers` Democratic leadership style on Teachers` Performance. This study involved descriptive method and quantitative approach. 66 Head Teachers and 2907 Teachers of the Public Secondary schools in Hyderabad District were the group of interest. Used random sampling technique, applying Rule of Thumb. John curry, (2006) describes that 1-100, 100% and 1000-5000, 5% Population is selected as sample keeping in view the 66 HTs and 154 Teachers were selected. The research instrument used was questionnaire Likert scale 5.0. It was revealed that the democratic leadership style proves to be effective for better teachers` performance. The head teacher should use democratic leadership style to carry out institutional matters effectively.